2013
DOI: 10.4054/demres.2013.28.36
|View full text |Cite
|
Sign up to set email alerts
|

Daughter preference in Japan: A reflection on gender role attitudes?

Abstract: BACKGROUNDUnlike other East Asian nations where preference for sons over daughters still prevails, gender preference for children in Japan has progressively shifted from son preference to a noticeable daughter preference over the past few decades. This emergence of daughter preference is surprising given that gender relations are more traditional in Japan than in other advanced countries. OBJECTIVEI focus on the extent to which individuals' gender preferences are shaped by their gender role attitudes and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
4
23
0
1
Order By: Relevance
“…Studies have show that the extent of son preference can change with evolving social values over time, including son preference in the cases of Japan and South Korea (Kureishi and Wakabayashi, 2011;Choi and Hwang, 2015). Indeed, recent research has confirmed a shift away from son preference (Kureishi and Wakabayashi, 2011) with some evidence of daughter preference now among certain groups in Japanese society (Fuse, 2013). Similarly, son preference in Korea has noticeably declined over time and consistent with this pattern, we find evidence of son preference among immigrants from Korea only when we examine the full period from 1980 to 2017.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Studies have show that the extent of son preference can change with evolving social values over time, including son preference in the cases of Japan and South Korea (Kureishi and Wakabayashi, 2011;Choi and Hwang, 2015). Indeed, recent research has confirmed a shift away from son preference (Kureishi and Wakabayashi, 2011) with some evidence of daughter preference now among certain groups in Japanese society (Fuse, 2013). Similarly, son preference in Korea has noticeably declined over time and consistent with this pattern, we find evidence of son preference among immigrants from Korea only when we examine the full period from 1980 to 2017.…”
Section: Introductionsupporting
confidence: 83%
“…1 In the case of Japan, son preference appears to have given way to daughter preference along some dimensions (Fuse, 2013). 2 For example, Dahl and Moretti (2008) present evidence of weaker forms of son preference among parents in the United States by estimating the effects of child gender on mothers' marital status and family structure using the 1960-2000 US Censuses.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is no evidence of son preference in Japan and recent data suggest that, if anything, Japanese parents appear to have a preference for daughters. Among those who desire one child, the proportion desiring a girl has gone from 20% in 1980 to 70% in 2002 (Fuse 2013). Fuse (2013) speculates that this may not necessarily reflect a desire raise daughters, but rather a desire to avoid the costs and pressures of raising boys to succeed in Japan’s highly competitive education system.…”
Section: Explanations For Trends In Marriage and Fertilitymentioning
confidence: 99%
“…Among those who desire one child, the proportion desiring a girl has gone from 20% in 1980 to 70% in 2002 (Fuse 2013). Fuse (2013) speculates that this may not necessarily reflect a desire raise daughters, but rather a desire to avoid the costs and pressures of raising boys to succeed in Japan’s highly competitive education system. The argument is that it is easier and safer to raise girls and that daughters are also desirable as a source of old-age support and companionship in a context where concerns about old age security focus less on financial concerns than on health care and companionship.…”
Section: Explanations For Trends In Marriage and Fertilitymentioning
confidence: 99%
“…Some countries of Eastern and Southern Asia have received particular attention in that regard (see, for example, Guilmato 2010;Jiang, Li, and Feldman 2011) and there is evidence of the use of abortion by emigrants from those countries who are resident elsewhere: Dubuc and Coleman (2007); Almond and Edlund (2008); Abrevaya (2009);Almond, Edlund, and Milligan (2013); Ray, Henry, and Urquia (2012). (While male preference has received most of the attention in the literature, including the present paper, female preference is certainly possible also; see Fuse 2013, for evidence of that from Japan.) Yamaguchi (1989) explored the effects of stopping rules on birth order and number of siblings in the absence of direct parental control over the sex probabilities.…”
Section: Introductionmentioning
confidence: 94%